Scour at bridge foundations on rock - Keaton, Jeffrey R. (Report (National Cooperative Highway Research Program), 2012)
"This report provides a methodology for estimating the time rate of scour and the design scour depth for a bridge founded on rock, as well as design and construction guidelines for application of the methodology. It will be of interest to hydraulic, bridge, and geotechnical engineers responsible for designing bridge foundations on rock or maintenance engineers concerned about existing bridges founded on erodible rock."--Foreword.